Corporate Governance Disclosure Practices and Their Determinant Factors in European Emerging Countries - Ruxandra-Adriana Mateescu (Journal of Accounting and Management Information Systems (JAMIS), 2015)
This paper investigates the corporate governance voluntary and non-voluntary disclosure practices of the listed companies from four European emerging countries, namely Estonia, Poland, Hungary and Romania. The study also identifies how compliant are the companies from these countries with their national corporate governance recommendations, including the compulsory corporate governance information, but also how willing they are to disclose voluntary corporate governance information. Finally, the paper aims to analyse the factors that influence companies from these countries to disclose certain types of information, trying to discover whether the companies' corporate governance systems are mostly influenced by their national business or legal environment or if there are more powerful internal factors which influence the enforcement of certain corporate governance practices.
Keywords: G32; M41; 650; corporate governance; transparency; compliance; institutional investors; firm-level variables; country-level variables